The epidemiology of airplane headache: A cross-sectional study on point prevalence and characteristics in 50, 000 travelers. (September 2022) - Konrad, Fabian; Moritz, Andreas; Moritz, Michael; Keunecke, Johann Georg; Tischler, Felix; Prottengeier, Johannes
Background: The current knowledge on the epidemiology and clinical manifestation of airplane headache is mostly derived from case series and small cohort studies without evidence from large populations. Methods: This cross-sectional study was conducted over a five-month period in the arrival area of two international airports in Germany. 50, 000 disembarking passengers were addressed about headaches during their flight to determine headache prevalence, and those confirming and willing to participate underwent a structured interview. Results: Headache during travel was reported by 374 passengers (0.75%), and 301 underwent a structured interview. One hundred and one (0.2%) met the diagnostic criteria of airplane headache. Six passengers suffered from migraines and 134 from tension-type headaches. The differences in the age and gender distribution between the airplane headache and non-airplane headache groups were not statistically significant. The onset (79.2%), duration (82.2%), and location (73.3%) of airplane headache mostly complied with current diagnostic criteria but pain intensity (42.6%) and quality (42.6%) did less so. Conclusion: Our data suggest a substantially lower prevalence of airplane headaches than previously reported. The pain intensity and quality seem less characteristic than assumed, suggesting a need to refine the current diagnostic criteria.